Agar extraction from integrated multitrophic aquacultured Gracilaria vermiculophylla: Evaluation of a microwave-assisted process using response surface methodology - Sousa, Ana M. M. (2013)
Microwave-assisted extraction (MAE) of agar from Gracilaria vermiculophylla, produced in an integrated multitrophic aquaculture (IMTA) system, from Ria de Aveiro (northwestern Portugal), was tested and optimized using response surface methodology. The influence of the MAE operational parameters (extraction time, temperature, solvent volume and stirring speed) on the physical and chemical properties of agar (yield, gel strength, gelling and melting temperatures, as well as, sulphate and 3,6-anhydro-Lgalactose contents) was evaluated in a 2^4 orthogonal composite design. The quality of the extracted agar compared favorably with the attained using traditional extraction (2 h at 85ºC) while reducing drastically extraction time, solvent consumption and waste disposal requirements. Agar MAE optimum results were: an yield of 14.4 ± 0.4%, a gel strength of 1331 ± 51 g/cm2, 40.7 ± 0.2 _C gelling temperature, 93.1 ± 0.5ºC melting temperature, 1.73 ± 0.13% sulfate content and 39.4 ± 0.3% 3,6-anhydro-L-galactose content. Furthermore, this study suggests the feasibility of the exploitation of G. vermiculophylla grew in IMTA systems for agar production.